REVITALISASI PASAR DATAH MANUAH KOTA PALANGKA RAYA BERBASIS PENGUATAN TATA KELOLA PASAR RAKYAT: Revitalization of Datah Manuah Market in Palangka Raya City Based on Strengthening Public Market Governance - Lesa, Heret (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2026)
Datah Manuah Market in Palangka Raya City is a strategic traditional market that plays an important role in supporting community economic activities and the delivery of public services in the trade sector. However, market revitalization efforts implemented to date have largely focused on physical improvements and have not been fully directed toward strengthening a sustainable market management system. This condition underscores the need for a more integrated traditional market revitalization policy that is based on governance strengthening. This policy paper aims to formulate strategic directions for the revitalization of Datah Manuah Market that are effective and sustainable, based on strengthening traditional market governance. A public policy approach is applied by considering the level of urgency, severity, and potential development of existing issues, and by referring to the policy analysis framework of William N. Dunn. The policy focus is directed toward strengthening market management institutions, the consistent implementation of standard operating procedures for market management, and the integration of market management into regional policies and development planning documents. The revitalization of Datah Manuah Market is positioned as part of regional public policy encompassing phased physical restructuring, strengthened market governance, and the development of promotion and identity for traditional markets. The implementation of this policy is expected to improve the quality of public services, enhance the competitiveness of traditional markets, and support sustainable regional economic development in Palangka Raya City.